Esophagectomy with gastroplasty in advanced megaesophagus: late results of omeprazole use - Pochini,Celso de Castro (2015)
Objective: To analyze the late results of advanced Chagasic megaesophagus treatment by esophagectomy associated with the use of proton pump inhibitor (omeprazole) as for the incidence of esophagitis and Barrett's esophagus in the remaining stump. Methods : We studied patients with advanced megaesophagus undergoing esophagectomy and transmediastinal esophagogastroplasty. Patients were divided into three groups: A (20) with esophageal replacement by full stomach, without the use of omeprazole; B (20) with esophageal replacement by full stomach, with omeprazole 40 mg/day introduced after the first postoperative endoscopy and maintained for six years; and C (30) with esophageal replacement by gastric tube with use of omeprazole. Dysphagia, weight loss and BMI were clinical parameters we analyzed. Upper gastrointestinal endoscopy was performed in all patients, and determined the height of the anastomosis, the aspect of the mucosa, with special attention to possible injuries arising from gastroesophageal reflux, and the patency of the esophagogastric anastomosis. Results : We studied 50 patients, 28 males (56%) and 22 (44%) females. All underwent endoscopy every year. In the first endoscopy, erosive esophagitis was present in nine patients (18%) and Barrett's esophagus, in four (8%); in the last endoscopy, erosive esophagitis was present in five patients (8%) and Barrett's esophagus in one (2%). When comparing groups B and C, there was no evidence that the manufacturing of a gastric tube reduced esophagitis and Barrett's esophagus. However, when comparing groups A and C, omeprazole use was correlated with reduction of reflux complications such as esophagitis and Barrett's esophagus (p <0.005). Conclusion : The use of omeprazole (40 mg/day) reduced the onset of erosive esophagitis and Barrett's esophagus during the late postoperative period.